Identification of effluent organic matter fractions responsible for low-pressure membrane fouling - Filloux, E.; Gallard, H.; Croue, Jean-Philippe (2012)
Anion exchange resin (AER), powder activated carbon (PAC) adsorption and ozonation treatments were applied on biologically treated wastewater effluent with the objective to modify the effluent organic matter (EfOM) matrix. Both AER and PAC led to significant total organic carbon (TOC) removal, while the TOC remained nearly constant after ozonation. Liquid Chromatography-Organic Carbon Detection (LC-OCD) analysis showed that the AER treatment preferentially removed high and intermediate molecular weight (MW) humic-like structures while PAC removed low MW compounds. Only a small reduction of the high MW colloids (i.e. biopolymers) was observed for AER and PAC treatments. Ozonation induced a large reduction of the biopolymers and an important increase of the low MW humic substances (i.e. building blocks).Single-cycle microfiltration (MF) and ultrafiltration (UF) tests were conducted using commercially available hollow fibres at a constant flux. After reconcentration to their original organic carbon content, the EfOM matrix modified by AER and PAC treatments exhibited higher UF membrane fouling compared to untreated effluent; result that correlated with the higher concentration of biopolymers. On the contrary, ozonation which induced a significant degradation of the biopolymers led to a minor flux reduction for both UF and MF filtration tests. Based on a single filtration, results indicate that biopolymers play a major role in low pressure membrane fouling and that intermediate and low MW compounds have minor impact. Thus, this approach has shown to be a valid methodology to identify the foulant fractions of EfOM. © 2012 Elsevier Ltd.